1996
DOI: 10.1016/0014-5793(96)01100-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of a cDNA encoding rat mitochondrial GrpE, a stress‐inducible nucleotide‐exchange factor of ubiquitous appearance in mammalian organs

Abstract: In contrast to the E. coli chaperones DnaK, GroEL and GroES, cDNAs encoding mitochondrial homologues of DnaJ and GrpE from higher eukaryotes have yet to be reported. Based on peptide sequences, we have isolated a cDNA encoding a 217 residue nuclear encoded precursor of rat mitochondrial GrpE (mt-GrpE) including a typical mitochondrial presequence of 27 residues. Western blotting revealed that the 21 kDa GrpE homologue is present exclusively in the mitochondrial fraction where it comprises only ~ 0.03% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…When compared with 13 additional bacterial GrpE sequences (Naylor et al, 1996), only 5 residues among a total of 32 GrpE sequences were found to be strictly conserved. Furthermore, three residues (Y176, Y180, and R212) in Chlamydomonas CGE1 and one residue (F188) in yeast Mge1p were identified that occur exclusively in cyanobacterial/chloroplastic and mitochondrial GrpE homologs, respectively; therefore, they may provide specific signatures for these homologs (Figure 10, bottom line of alignment).…”
Section: Cge1 Complements the Temperature-sensitive Phenotype Of E Cmentioning
confidence: 94%
See 4 more Smart Citations
“…When compared with 13 additional bacterial GrpE sequences (Naylor et al, 1996), only 5 residues among a total of 32 GrpE sequences were found to be strictly conserved. Furthermore, three residues (Y176, Y180, and R212) in Chlamydomonas CGE1 and one residue (F188) in yeast Mge1p were identified that occur exclusively in cyanobacterial/chloroplastic and mitochondrial GrpE homologs, respectively; therefore, they may provide specific signatures for these homologs (Figure 10, bottom line of alignment).…”
Section: Cge1 Complements the Temperature-sensitive Phenotype Of E Cmentioning
confidence: 94%
“…In E. coli , the GrpE protein is induced by heat stress (Ang et al, 1986), but this is not the case for its mitochondrial counterparts from yeast or rat (Ikeda et al, 1994;Naylor et al, 1996). To study the expression pattern of the CGE1 gene, we analyzed the accumulation of the CGE1 transcript in Chlamydomonas cells that had been shifted from 25 to 40 Њ C or that had been shifted to the light after 15 hr of dark adaptation.…”
Section: Cge1 Is Encoded By a Single-copy Gene That Is Inducible By Hmentioning
confidence: 99%
See 3 more Smart Citations